Strengthening labour and welfare institutions in times of global economic crisis: experiences and lessons learnt - Sudan, Falendra Kumar (Economic Journal of Development Issues, 2012)
The present paper intends to examine the labour market scenario in the context of the global financial and economic crisis, social protection during crisis, responses to the economic crisis at different levels, and the lessons learnt to protect workers, families and societies from the negative repercussions of this crisis and in the future. The current global financial crisis has quickly spread from its origin in the United States to the global economy, resulting in collapsed aggregate demand and freezing of credit channels. Consequently, millions of workers around the globe have been laid off, or for those lucky enough to have held on to their jobs, many have experienced cuts in hours worked, wages and other benefits. Though there are increasing signs that the major economies are exiting recession, the weakness of the labour market will remain a key challenge for governments in the years to come, particularly in terms of vulnerable groups such as youth. Over the medium? and long?term, governments should also aim to develop a comprehensive and integrated policy and institutional framework that will enable them to better respond to crises, emanating from not only global shocks but also those arising from local and regional phenomena. This involves the development of labour market institutions and a broad?based social security system, which acts as an automatic stabilizer during a crisis. In developing countries, barriers to formalization need to be reduced to ensure that workers have more opportunities to find decent jobs and be protected by labour market institutions, including social protection measures. Finally, the policy response should be the outcome of constructive dialogue between the social partners. Key words: Labour and Welfare Institutions; Strengthening; Global Economic Crisis; Experiences; Lessons Economic Journal of Development Issues Vol. 11 & 12 No. 1-2 (2010) Combined Issue Page: 33-46 Uploaded date: 10 April, 2012